(untitled) (International Seven Journal of Multidisciplinary, 2024)
Objective: To analyze autism spectrum disorder and early diagnosis: Literature Review: Autism is defined as a complex developmental disorder, from a behavioral point of view, with different etiologies that manifests itself in varying degrees of severity (GADIA, 2006). The characteristics of the spectrum are persistent impairments in communication and social interaction, as well as in behaviors that may include interests and activity patterns, symptoms that are present since childhood and limit or impair the individual’s daily functioning (APA, 2014). The subcategories are part of ASD, and impairment can occur at three levels of severity. Final considerations: The importance of early diagnosis of ASD is highlighted, which tends to seek and collect more information about the established diagnosis. It is understood that the earlier the child is diagnosed and starts treatment, the greater the possibilities of development within their physical and mental capacities. The choice of appropriate treatment is extremely important, as ASD accompanies the individual throughout his or her life.